Penciptaan Busana Pesta Malam dengan Sumber Ide Bunga Aster - Rufaydah, Indana; Wahyuningsih, Urip (Universitas Negeri Surabaya, 2023)
Daisies are often referred to as stars, have many types of colors that make anyone stunned to see them. With its beauty, daisies are used as a source of ideas for the creation of a collection of evening party dresses. This study aims to determine the process of creating an evening party dress design with the source of the daisy flower idea. This research method uses the Double Diamond Design Process, which is divided into 4 stages, including discover, which is an exploration of the theme discussed in this study, namely